Inhibitory activity of the ethanolic extract of Cyperus Rotundus from the Cajamarca region (Contumazá province) in a standardize strain of Streptococcus mutans (ATCC®25175) - Bazán Aliaga, Rosita Belén (2022)
Objective: The purpose of this study was to determine in vitro the inhibitory activity of the ethanolic extract of Cyperus rotundus (Cajamarca - Contumazá) against a standardize strain of Streptococcus mutans (ATCC®25175™). Materials and methods: This study was an experimental in vitro study, which consisted of determining the inhibitory effect of three concentrations of the ethanolic extract of Cyperus rotundus: 250 mg/ml, 500 mg/ml, and 1000 mg/ml against a strains of Streptococcus mutans (ATCC®25175™). Ten tests were performed for each concentration, having 0.12% chlorhexidine as a positive control for Streptococcus mutans plates and 10% DMSO as a negative control. To evaluate the inhibitory effect, the disk diffusion method or Kirby-Bauer test was used, reading the results at 48 hours after initial sowing. Results: None of the three concentrations of the ethanolic extract of Cyperus rotundus demosntrated inhibitory effects on the Streptococcus mutans strain; however, the positive control, chlorhexidine, clearly showed inhibition halos of 14.43 mm ± 1.23 mm after 48 hours of incubation. Conclusions: The ethanolic extract of Cyperus rotundus did not inhibit the growth of Streptococcus mutans. It is recommended to deepen the chemical analysis of the components of this plant and explore other extraction methods to verify its bacteriostatic action versus other oral and non-oral microorganisms.